Keratin 8/18a.1 Expression Influences Embryonic Neural Crest Cell Dynamics and Contributes to Postnatal Corneal Regeneration in Zebrafish - Antionette L. Williams; Brenda L. Bohnsack (Cells, 2024)
A complete understanding of neural crest cell mechanodynamics during ocular development will provide insight into postnatal neural crest cell contributions to ophthalmic abnormalities in adult tissues and inform regenerative strategies toward injury repair. Herein, single-cell RNA sequencing in zebrafish during early eye development revealed keratin intermediate filament genes krt8 and krt18a.1 as additional factors expressed during anterior segment development. In situ hybridization and immunofluorescence microscopy confirmed krt8 and krt18a.1 expression in the early neural plate border and migrating cranial neural crest cells. Morpholino oligonucleotide (MO)-mediated knockdown of K8 and K18a.1 markedly disrupted the migration of neural crest cell subpopulations and decreased neural crest cell marker gene expression in the craniofacial region and eye at 48 h postfertilization (hpf), resulting in severe phenotypic defects reminiscent of neurocristopathies. Interestingly, the expression of K18a.1, but not K8, is regulated by retinoic acid (RA) during early-stage development. Further, both keratin proteins were detected during postnatal corneal regeneration in adult zebrafish. Altogether, we demonstrated that both K8 and K18a.1 contribute to the early development and postnatal repair of neural crest cell-derived ocular tissues.